Mal de meleda with congenital cataract: A novel case report - Anisha Sethi; Jaspreet Kaur Janda; Nidhi Sharma; S K Malhotra (Wolters Kluwer Medknow Publications, 2015)
Mal de meleda (MdM), a rare autosomal recessive genodermatosis is characterized by erythema and hyperkeratosis of the palms and soles with a sharp demarcation and that progress with age (progrediens) and extend to the dorsal aspects of the hands and feet (transgrediens). It has been associated with various conditions albeit rarely with congenial cataract. Ocular lens and the skin have the same embryological origins. We hereby present this novel case report of Mal de meleda in association with congenital posterior subcapsular cataract which to the best of our knowledge has not been reported from India before.